The concept of reflection: a systematic review and thematic synthesis across professional contexts. Issue 3 (4th May 2019) - Marshall, Tony
ABSTRACT: Reflection is widely endorsed by professional bodies and practitioners are required to document professional learning to evidence standards of professionalism. Due to the lack of a consensual definition for reflection, there is confusion regarding 'what reflection is'. Prior to the development of an empirical evidence base that explores reflection, it is important to develop a consensually agreed concept and definition to guide experimental research. The aim of this systematic review is to understand the concept of reflection by performing a synthesis of existing conceptually oriented qualitative studies. Fourteen sources were included in a thematic synthesis that resulted in the construction of four analytical themes: cognitive, integrative, iterative and active. These themes were explored in relation to existing research and a novel definition of reflection was proposed. It is hoped that this review will encourage further enquiry into the concept and process of reflection.